MANIPULATION OF CULTURAL PRACTICES FOR IPIL-IPIL AND ITS EFFECT ON THE INTERCROPPED CASSAVA - Escalada, Rodolfo G. (Annals of Tropical Research, 1981)
Pruning and intercropping affected plant height and fresh herbage yield of ipil-ipil. Both parameters declined as the crop was cut back periodically. Plant population also compounded the effect. At high plant population, the pruned plants developed thin and elongated stems which reduced herbage yield per plant per unit area. However, the higher number of plants per unit area compensated for the reduced vegetative growth. High herbage yields were obtained at close planting distance. The cassava plants competed intensely with ipil-ipil for light and space. Due to rapid growth and development of the pruned ipil-ipil, growth and development of plant parts and formation of cassava tubers were greatly affected as manifested by the higher yield of the monoculture crop. A planting distance of 3 m x 15 cm for ipil-ipil resulted in the production of reasonable tuber yields per hectare of cassava.